2021
DOI: 10.1111/petr.13995
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes using unmanipulated haploidentical hematopoietic stem cells combined with third‐party umbilical cord blood transplantation for non‐malignant diseases in children: The experience of a single center

Abstract: Background: Unmanipulated haploid HSCT for SAA has resulted in improved outcomes over recent years. However, studies related to unmanipulated haploid HSCs combined with tp-UCB transplantation for other types of NMD are rare. Accordingly, we present the outcomes of 109 pediatric patients with life-threatening NMD undergoing unmanipulated haploid HSCs combined with tp-UCB transplantation.Procedure: We retrospectively investigated 109 pediatric patients with lifethreatening NMD treated with unmanipulated haploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…In patients with a successful engraftment, the incidence of aGVHD and moderate-to-severe cGVHD was similar between the haplo-HSCT and haplo-cord-HSCT groups, while the overall cGVHD in the haplo-cord-HSCT group tended to be lower than that observed in the haplo-HSCT group. These findings are consistent with those reported by an earlier study ( 15 ). This may be because UCB contains MSCs and CD4 + CD25 + Tregs ( 29 , 30 ), which have an immune regulatory role on the hematopoietic microenvironment and prevention of GVHD.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In patients with a successful engraftment, the incidence of aGVHD and moderate-to-severe cGVHD was similar between the haplo-HSCT and haplo-cord-HSCT groups, while the overall cGVHD in the haplo-cord-HSCT group tended to be lower than that observed in the haplo-HSCT group. These findings are consistent with those reported by an earlier study ( 15 ). This may be because UCB contains MSCs and CD4 + CD25 + Tregs ( 29 , 30 ), which have an immune regulatory role on the hematopoietic microenvironment and prevention of GVHD.…”
Section: Discussionsupporting
confidence: 94%
“…Several single-arm studies have demonstrated the feasibility and effectiveness of haplo-cord-HSCT in SAA and other nonneoplastic and malignant hematologic disorders (13)(14)(15)17). However, this approach for SAA is currently considered investigational and requires further study before firm recommendations can be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CB was associated with a higher GF rate and inferior platelet engraftment. In a study from 2021, HCT in 60 pediatric patients with SAA used unmanipulated haploHCT with third-party 1-5/6 HLA antigen-matched umbilical CB after myeloablative conditioning with busulfan, Cy, and Flu (228). The 5-year transplant-related mortality, OS, and FFS were 2.8%, 97.2%, and 96.2%, respectively.…”
Section: Cord Blood Transplantationsmentioning
confidence: 99%